Big Five Personality Traits and Financial Risk Tolerance among Nepalese Retail Investors - Sharma, Pooja; Basnet, Dinesh (International Journal of Atharva, 2026)
Purpose: Personality traits are the core predictors of individual’s financial risk tolerance, but they are less examined in prior research pertaining to Nepal. Thus, this research examines the effect of Openness to Experience, Conscientiousness, Extraversion, Agreeableness, and Neuroticism on the financial risk tolerance of Nepalese retail investors. Research Design: This study followed positivist philosophy, deductive approach and employed descriptive and causal research designs. Two hundred and seventy-two stock market investors participated in this study where responses were gathered using self-administered questionnaire utilizing a five-point Likert Scale. Statistical techniques such as descriptive analysis, correlation analysis, multicollinearity testing, and regression analysis were applied using SPSS. Findings: The findings indicated that Openness to Experience, Conscientiousness, and Extraversion positively and significantly influence Financial Risk Tolerance. Agreeableness demonstrated a negative but statistically insignificant relationship with Financial Risk Tolerance, whereas Neuroticism showed a significant negative relationship. The regression model explained about 39% of the variation in financial risk tolerance and was statistically significant. The Cronbach’s alpha showed acceptable internal consistency and there were no multicollinearity issues among predictors. Implications: Understanding how personality traits affect Financial Risk Tolerance can contribute to behavioral economics by challenging canonical finance models. This study is imperative for individuals because it can largely shape how they participate in stock investment, avoid impulsive financial practices, and eventually know their risk-bearing capacity. Furthermore, the findings can assist financial institutions in providing personalized investment to their stakeholders.